Partisipasi Masyarakat Berbasis Kearifan Lokal dalam Menumbuhkan Demokrasi di Kebumen - Arif Widodo (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2021)
The undemocratic 2020 regional elections in Kebumen with a single candidate gave birth to the Community of Empty Boxes (Mas Koko) movement, which metamorphosed into the Konco Coalition of Democracy Fighters (Koko Pede) in Kebumen Regency. The momentum that paved the way for the Kebumen people's struggle so that the next local election does not present a single candidate. The results of this study are the continuity of democracy guarding by Koko Pede, after the election of the single candidate Arif Sugiyanto-Ristawati Purwaningsih as regent and deputy regent of Kebumen. This non-institutionalized movement is also an integral part of community participation based on local wisdom in fostering democracy in Kebumen. The implementation of this movement is by cooperating with other elements of society, including students, to carry out moral movements through various activities, such as discussions, both offline and online on social media (Medsos), whose recommendations reject a single candidate. Apart from that, he is cooperating with figures to carry out motions of no confidence against parties that carry out undemocratic political practices. This includes legislators from political parties who have submitted a single candidate in the 2020 Kebumen local elections.Furthermore, preparing candidates through an independent route, if all political parties submit a single candidate again in the next regional election. Even if the implementation coincides with the 2024 general election and presidential election, Koko Pede will make an even bigger move to reject a single candidate